Effects of the COVID-19 pandemic on elderly patients with head and neck squamous cell carcinoma - Ye, Pei-Jing; Xi, Yan; Sun, Chuan-Zheng; Lei, Qian; Li, Lei (Frontiers in Oncology, 2022)
Background: This study aimed to assess the impact of COVID-19 on elderly patients with head and neck squamous cell carcinoma (HNSCC) in our center. Methods: This retrospective study analyzed the clinical characteristics of 400 elderly patients with HNSCC, calculated their treatment interruption rates, and compared the time of delayed diagnosis. Results: The rate of elderly patients with HNSCC with a delayed diagnosis was higher in the "during the COVID-19 pandemic" group than in the "before the COVID-19 pandemic" group, the difference was statistically significant (p=.0017). There was a substantial difference in the rate of treatment interruption between the two groups (p=.002). Conclusions: This is the first study to explore the effect of the COVID-19 pandemic on visits and treatment interruptions in elderly patients with HNSCC. The current impact of the COVID-19 pandemic on HNSCC treatment has resulted in reductions and delays in diagnosing cancer and providing treatment.